Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s12298-014-0239-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide increases tolerance responses to moderate water deficit in leaves of Phaseolus vulgaris and Vigna unguiculata bean species

Abstract: Drought stress is one of the most intensively studied and widespread constraints, and nitric oxide (NO) is a key signaling molecule involved in the mediation of abiotic stresses in plants. We demonstrated that a sprayed solution of NO from donor sodium nitroprusside increased drought stress tolerance responses in both sensitive (Phaseolus vulgaris) and tolerant (Vigna unguiculata) beans. In intact plants subjected to halting irrigation, NO increased the leaf relative water content and stomatal conductance in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Subsequently, several studies suggested the generation of NO in guard cells in response to drought and ABA [30,34,54]. The accumulation of NO has often been visualized in guard cells in response to water deficit by using a NO-sensitive fluorescent dye DAF-2DA [10,15,16,23,40].…”
Section: No As a Modulator Of Stomatal Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, several studies suggested the generation of NO in guard cells in response to drought and ABA [30,34,54]. The accumulation of NO has often been visualized in guard cells in response to water deficit by using a NO-sensitive fluorescent dye DAF-2DA [10,15,16,23,40].…”
Section: No As a Modulator Of Stomatal Movementmentioning
confidence: 99%
“…[18,25,35]. An antioxidant function was often attributed to NO due to its ability to protect plants from stress-induced oxidative damage [2,14,34]. NO alleviated the ROS-mediated cytotoxic processes in Solanum tuberosum leaves and inhibited cell death, ion leakage, and DNA fragmentation [35].…”
Section: No As An Antioxidantmentioning
confidence: 99%
“…It is possible that the attenuation of the harmful effects of water deficit on the growth of seedlings from seeds pretreated with SNP could occur due to changes in gas exchange since numerous studies have shown that NO plays an important role in the regulation of stomatal movement under stress conditions (Zimmer-Prados et al, 2014;Wang et al, 2015). μmol.L -1 SNP increased the carotenoid content in the leaves in both conditions compared to that in NT ( Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Although initial discoveries in plants recognized NO as an atmospheric toxic pollutant for plant foliage, it was eventually considered as a modulator of plant defense during pathogen attacks. The increasing number of reports demonstrated the role of NO in a plethora of plant development processes including seed germination (Arc et al, 2013), root formation, different stages of the seed development, gravitropism, stomatal movements, photosynthesis, mitochondrial functionality, senescence, plant maturation (Sun et al, 2017;Patel et al, 2017;Hasanuzzaman et al, 2018;Locato et al, 2016;Mostofa et al, 2015;Asgher et al, 2017), multiple abiotic (Fancy et al, 2017;Santisree et al, 2015;Parankusam et al, 2017;Adimulam et al, 2017;Tossi et al, 2012;Sehrawat et al, 2013;Ziogas et al, 2013) and biotic stress responses in plants (Vaishnav et al, 2018). In addition, a number of studies focused on describing the crucial role of NO in moderating various plant hormone-mediated development and stress responses (Asgher et al, 2017).…”
Section: Nitric Oxide Function In Plantsmentioning
confidence: 99%
“…The application of Diethylenetriamine-NONOate (DETA/NO) ameliorated long term salinity effects in Glycene max via the induction of antioxidant enzymes (Egbichi et al, 2014). Studies have provided evidence that NO mediated detoxification is partly by its ability to regulate ascorbateÀglutathione cycle through S-nitrosylation (Camejo et al, 2013;Ziogas et al, 2013). It is evident from the studies that salt stress induces an increase in total S-nitrosylation especially S-nitrosylation of the glycine dehydrogenase P subunit, F1 ATPase β subunit, and isocitrate dehydrogenase (ICDH) implying the role of NO-mediated posttranslational modifications in controlling respiratory/ photorespiratory pathways (Fares et al, 2011;Camejo et al, 2013;Abat and Deswal, 2009;Begara-Morales et al, 2015).…”
Section: No In Plant Salt Stress Tolerancementioning
confidence: 99%